2021
DOI: 10.1007/s00190-021-01583-9
|View full text |Cite
|
Sign up to set email alerts
|

GNSS satellite inter-frequency clock bias estimation and correction based on IGS clock datum: a unified model and result validation using BDS-2 and BDS-3 multi-frequency data

Abstract: To deal with inconsistency between Global Navigation Satellite System (GNSS) multi-frequency data and International GNSS Service (IGS) clock product, we propose a unified model for GNSS satellite inter-frequency clock bias (IFCB) estimation and correction based on the IGS clock datum. The proposed model is rigorously derived by three sequential steps. First, by means of accurate modeling of the time-variant part of satellite phase-based IFCB (PIFCB) and introducing a zero-mean condition for satellite code-base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…Currently, rich studies about GNSS multi-frequency IFCBs have been reported, e.g., Guo et al (2017), Gong et al (2020) and Fan et al (2021). Results demonstrate that GPS and GLONASS satellites exhibit significant IFCB variations, they may vary up to 2 and 5 dm (Zhang et al 2021(Zhang et al , 2022, while that of BDS-3 and Galileo satellites are marginal and even can be ignored.…”
Section: Calculation Of Gnss Ifcbsmentioning
confidence: 99%
“…Currently, rich studies about GNSS multi-frequency IFCBs have been reported, e.g., Guo et al (2017), Gong et al (2020) and Fan et al (2021). Results demonstrate that GPS and GLONASS satellites exhibit significant IFCB variations, they may vary up to 2 and 5 dm (Zhang et al 2021(Zhang et al , 2022, while that of BDS-3 and Galileo satellites are marginal and even can be ignored.…”
Section: Calculation Of Gnss Ifcbsmentioning
confidence: 99%